Analysis of the Implementation of Article 22 of Law Number 23 of 2011 Concerning Management of Zakat as a Reduction of Taxable Income in the City of Palu From Maqāṣhid Al-Syarīʿah Perspective - Sari Sakinah; Zainal Abidin; Gani Jumaat; Fatimawali, Fatimawali; Ermawati, Ermawati (State Islamic University Datokarama Palu, 2024)
Zakat is the third pillar of Islam, so most Muslims know the importance of paying Zakat. Indonesia has related regulations, namely Law of the Republic of Indonesia No. 23 of 2011 concerning the management of Zakat; Article 22 states,